Propuesta de diseño curricular - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2009)
Abstract. The history of the process of curricular redesign of the department of sociology of the University of Antioch is necessary by the end of to overcome it the last decade of century XX. The director of that moment Jaime Restrepo Fourth considered like one of his fundamental tasks, bound to his plan of development, modernizing the currículos of the academic units of the university. The declared intention was to direct itself towards a university ``for a new century of the lights', within this assignment he was essential to put to tone to the different programs of the university with the unquestionable realities of the modernization (or the posmodernización: according to is wanted it to conceive). Year 1999 was declared the year of the curricular renovation. Different academic events, among them an international seminary, laid the way of the curricular changes of the programs. Resumen. La historia del proceso de rediseño curricular del departamento de sociología de la Universidad de Antioquia es necesario remontarla a fines de la última década del siglo XX. El rector de ese momento Jaime Restrepo Cuartas consideró como una de sus tareas fundamentales, ligada a su plan de desarrollo, el modernizar los currículos de las unidades académicas de la universidad. El propósito declarado era el encaminarse hacia una universidad ‘‘para un nuevo siglo de las luces’’, dentro de este cometido era esencial poner a tono a los distintos programas de la universidad con las realidades indiscutibles de la modernización (o de la posmodernización: según se lo quiera concebir). El año 1999 fue declarado el año de la renovación curricular. Distintos eventos académicos, entre ellos un seminario internacional, abrieron el camino de los cambios curriculares de los programas.